Application of Apriori Algorithms on Online Shop Product Recommendation Systems (Case Study: Al-Veera Jember Muslim Clothing Store) - Muhyiy, Hafiidh; Sagirani, Tri; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
Online shop is a trend in the current era because customers can easily and easily buy the desired product, including the Al-Veera store in Jember. Because of their short operating hours and the small area of their marketing. Besides that they need applications that can provide product recommendations. Product recommendation applications using the Apriori Algorithm can be a solution to this problem. The Priori algorithm is a logic calculation which combines a particular product with other products through transaction history data. Based on the results of testing the Apriori Algorithm on Product Recommendation Applications, which were carried out in 5 stages in a priori the results showed that the Priori Algorithm runs according to the scenario generated from manual calculations. Thus it can be said that the application made is able to help Al-Veera stores in promoting their products